Implementing total quality management in Unit Trust Operations Department of PNB: a case study of Permodalan Nasional Berhad (PNB) / Zatul Akmar Razak - Razak, Zatul Akmar (2009)
This study is conducted to examine the success of implementing Total Quality Management in Unit Trust Operations Department of PNB. At PNB, total quality management is regarded as a totally integrated effort for gaining competitive advantage through continuous improvement of every aspect of the organizational business process. It is the foundation of this philosophy that has made PNB what it is today. From the passionately believes in putting the needs and requirements of its customers first. By employing a total quality management system that integrates fundamental management techniques, existing improvement efforts and technical tools under a disciplined approach focused on continuous improvement, PNB is confident in delivering customer satisfaction at all levels. TQM encourages participation amongst shop floor workers and managers. Quality is the outcome of all activities that take place within an organization, that all functions and all employees have to participate in the improvement process; that organizations need both quality systems and a quality culture. Product development in a TQM environment is very different to product development in a non-TQM environment. Without a TQM approach, product development is usually carried on in inconsistency environment where each department acts independently. Short-term results drive behavior so scrap, changes, work-arounds, waste, and rework are normal practice. Management focuses on supervising individuals, and fire-fighting is necessary and rewarded. Product development in a TQM environment is customer-driven and focused on quality. Teams are process-oriented, and interact with their internal customers to deliver the required results. Management's focus is on controlling the overall process, and rewarding teamwork.